Diagnostic Utility of Pre-Genomic Hepatitis B RNA in the Evaluation of HBV/HIV Coinfection - Kenneth Sherman; Susan Rouster; Heidi Meeds; Marion Peters; Jason Blackard; Paul Horn; Timothy Archampong; Awewura Kwara; Mark Anderson; Michael Stec; Gavin Cloherty (Case Western Reserve University, 2024)
Background: Newer biomarkers of Hepatitis B virus (HBV) infection and treatment response have not been well-characterized in individuals with HBV/HIV coinfection.  Methods: Pre-genomic RNA (pgRNA) and quantitative HBsAg (qHBsAg) were used to evaluate the associations with baseline characteristics. Participants included two separate groups - 236 with HBV/HIV coinfection enrolled in a cross-sectional cohort in Ghana and 47 from an HBV nucleoside/nucleotide treatment trial comparing tenofovir to adefovir in the United States. Results: In both cohorts, HBe antigenemia was highly associated with pgRNA and HBV DNA levels. In the treatment cohort, pre-treatment pgRNA serum concentration was 7.0 log10 U/mL, and mean qHBsAg was 201,297 IU/mL. The observed treatment-associated decrease in pgRNA was consistent with a biphasic decline curve that reached second-phase kinetics following treatment week 12. Changes from baseline were significantly correlated with changes in serum ALT (r = - 0.518; P = 0.023) but not with changes in HBV DNA (r = 0.132, P = NS). qHBsAg also correlated with ALT change (r = - 0.488, P = 0.034). Conclusion: pgRNA and qHBsAg represent newer biomarkers of HBV replication that may help monitor response and treatment outcomes. HBV pgRNA is highly associated with both HBeAg and ALT and may predict both active replication from the closed circular DNA (cccDNA) template as well as hepatic injury.